Genome-wide identification of antimicrobial peptides in the liver fluke, Clonorchis sinensis - Yoo, Won Gi (Bioinformation, 2015)
The increase in prevalence of antimicrobial resistance makes the search for new antibiotic agents imperative. Antimicrobial peptides (AMPs) from natural resources have been recognized as suitable tools to combat antibiotic-resistant bacteria. The liver fluke Clonorchis sinensis living in germ-filled environments could be a good source of antimicrobials. Here, we report the use of a rational protocol that combines AMP predictions based on their physicochemical properties and their in vivo stability to discover AMP candidates from the entire genome of C. sinensis. To screen AMP candidates, in silico analyses based on the physicochemical properties of known AMPs, such as length, charge, isoelectric point, and in vitro and in vivo aggregation values were performed. To enhance their in vivo stability, proteins having proteolytic cleavage sites were excluded. As a consequence, four high-activity, highstability peptides were identified. These peptides could be potential starting materials for the development of new AMPs via structural modification and optimization. Thus, this study proposes a refined computational method to develop new AMPs and identifies four AMP candidates, which could serve as templates for further development of peptide antibiotics.